On Composition of Natural Numbers - BAPAT, M.N.; SONWANE, R.K. (SCHOOL SCIENCE, 2006)
Nature manifests itself through a variety of things live, dead or in fossil forms and that too in several numbers. Here by number we mean “that handy device which helps us to judge and feel the  extent of its manifestation” .